2017
DOI: 10.1103/physreva.96.013823
|View full text |Cite
|
Sign up to set email alerts
|

Two-axis-twisting spin squeezing by multipass quantum erasure

Abstract: Many-body entangled states are key elements in quantum information science and quantum metrology. One important problem in establishing a high degree of many-body entanglement using optical techniques is the leakage of the system information via the light that creates such entanglement. We propose an all-optical interference-based approach to erase this information. Unwanted atom-light entanglement can be removed by destructive interference of three or more successive atom-light interactions, leaving behind on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
(72 reference statements)
0
22
0
Order By: Relevance
“…Recently, Wang et al [61] have shown that one can erase the remaining back-action of the two-pass scheme in a three-pass configuration to achieve unitary spinsqueezing of an atomic ensemble. With phase shifts φ ij between passes i and j, the full master equation in this case readsρ Setting φ 12 = φ 23 = φ, the solution is found to be φ = ±2π/3.…”
Section: Unconditional Squeezing Of a Single Oscillatormentioning
confidence: 99%
“…Recently, Wang et al [61] have shown that one can erase the remaining back-action of the two-pass scheme in a three-pass configuration to achieve unitary spinsqueezing of an atomic ensemble. With phase shifts φ ij between passes i and j, the full master equation in this case readsρ Setting φ 12 = φ 23 = φ, the solution is found to be φ = ±2π/3.…”
Section: Unconditional Squeezing Of a Single Oscillatormentioning
confidence: 99%
“…In these works the entangled state that is produced can be described within this approximation as a two-mode squeezed state. However, due to the fundamentally different nature of the spins to modes, it is well known that different dynamics can result for long evolution times, observed in effects such as oversqueezing [24][25][26][27][28][29]. Entanglement between different spatial regions of a single BEC was experimentally observed [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the control problem considered in this paper is not contained in the framework where the superiority of CF over MF (or the equivalency of CF and MF) has been proved [20, 24-26, 28, 33]. Also the proposed scheme is a sort of reservoir engineering but is different from the other approaches [35][36][37][38][39][40][41][42], in that it relies on a novel reservoir composed of the series of dispersive and dissipative couplings, inspired by the MF control composed of the QND measurement and the subsequent filtering process.…”
Section: Introductionmentioning
confidence: 99%